Let me count the ways: Expressing affinity in computer-mediated communication and face-to-face interaction - WALTHER, Joseph B (Institutional Knowledge at Singapore Management University, 2005)
Alternative views of computer-mediated communication suggest that it is devoid of affective cues and interpersonal expression, or that the translation of affect into verbal cues facilitates relational communication. Little research has examined basic affective communication online, mirroring a dearth of empirical research identifying spontaneous affective verbal cues in face-to-face interaction. An experiment prompted participants to enact greater or lesser affinity in face-to-face or synchronous computer chat dyads in order to assess the proportion of affect expressed verbally online compared to that which is verbal offline and the specific behaviors that account for affective communication in each channel.Partners’ ratings demonstrated affective equivalency across settings. Analyses of the verbal, kinesic, and vocalic behaviors of face-to-face participants and verbal transcripts from computer sessions revealed specific cues in each condition that led to these ratings. Results support a primary but previously untested proposition in the social information processing theory of mediated interaction.